DASAR-DASAR TEOLOGIS SUNNI UNTUK KONTEKS USAHA (Studi Gagasan Kyai Saleh Darat) - Rahmat Fajri (UIN Sunan Kalijaga Yogyakarta, 2015)
Most of Indonesian Muslims are adherents of ahlu as-sunnah wa al-jama’ah (Sunni). It is therefore easily to be assumed that Indonesian Muslim business- men are also the adherent of the Sunni Muslims groups. This paper explores theological belief systems of Asy’ariyah on work, responsibility and wealth. Muslim’s theological beliefs could explain the motivation of Muslims to work and obtain the wealth. Functionally, a belief that work is a form of individual responsibility, that work is the way to gain wealth, and that all Muslims must work would drive Muslims to active in productive ventures, instead of being fatalistic and mushy. Muslims should realize the important of wealth, because by owning the wealth they could actualize themselves and preclude them from scoundrelly conditions, while at the same time they should also aware that the wealth is belong to God.